Praktikalitas dan Efektivitas Media Pembelajaran Powerpoint-Ispring Terintegrasi Multipel Representasi Kimia Dan Pertanyaan Prompting Materi Sifat Koligatif Larutan Kelas XII MIPA SMA/MA - Khovifah Indah Pratiwi; Guspatni Guspatni (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The colligative of properties of solution is one of the mandatory materials in high school/MA level chemistry subjects in class XII. The concepts in the colligative properties of solutions are abstract, so it is often difficult for students to understand. To respond to the problems above, there has been the development of Microsoft PowerPoint-iSpring media that integrates prompting questions and three levels of chemical representation on the colligative properties of the solution, but the practicality and effectiveness tests have not been carried out. This study aims to demonstrate the practicality and effectiveness of the integrated PowerPoint-iSpring learning media with multiple chemical representations and prompt questions on the colligative properties of solutions on the learning outcomes of students in class XII science high school/MA. In this study, practicality and effectiveness tests were conducted. The effectiveness test used a pre-experimental design research design with one group pretest post-test research design. The educated population consisted of students in class XI IPA and XII MIPA at SMAN 2 Koto XI Tarusan and the sample was selected using the purposive sampling technique. The sample class in this study was class XII MIPA 3. The instrument for the practicality test was in the form of a questionnaire, while for the effectiveness test the instrument was in the form of a multiple choice test. The results of the study obtained a practicality value of 78.25 from teachers and students with practical categories based on practicality data analysis from practitioners and the integrated PowerPoint-iSpring learning media with multiple chemical representations and prompting questions on the material colligative properties of effective solutions in improving student learning outcomes in class XII IPA at SMAN 2 Koto XI Tarusan with an N-Gain score of 0.77 in the high category and analysis a t-test obtained that the pretest average was significantly smaller than the posttest average.